FREEDOM IN PRISON: THE TRANSFORMATIVE IMPACT OF PSIT (PSYCHO-SPIRITUAL INTEGRATIVE THERAPY) ON THE PSYCHOLOGICAL WELL-BEING OF INCARCERATED PEOPLE - Fridari, I Gusti Ayu Diah; Wilani, Ni Made Ari; Hartawan, Anak Agung Gede; Budd, Thomas Andrew (Jurnal Psikologi, 2022)
The department of counseling services at Kerobokan Prison, Bali, Indonesia reported to the researcher of this study that some of their inmates experienced psychological complaints which were impacting their physical health. The researcher conducted this study with the aim of providing a means of relief for the inmates, as well as to examine the impact of a Psycho-Spiritual Integrative Therapy (PSIT) as an intervention. A qualitative research method was used with a multiple case study approach with a thematic analysis to determine the influence of the intervention on the participants’ sense of life aspiration and psychological well-being. Fifteen male prisoners, who were serving 10 or more years for drug related offenses, completed the PSIT and participated in a post interview. The researcher found 5 main themes related to the participants’ experiences over the course of the intervention, which were regret, forgiveness, acceptance, belief, and affirmation. The participant reports indicate the beginning of a transformative change in perspective which may be beneficial for creating a new life for themselves upon their release from prison. Further research is necessary to assess long-term changes in the participants’ perspectives, and how they have integrated their awareness for their return to society. The findings of this research may be included into a residential health services module for the counseling services department at Kerobokan Prison, as well they may be influential in further public health research